EFFECT OF TRANS PRK ON TEAR FILM STABILITY - Syeda Iqra Iqbal; Zahid Siddiq; Bassam Mubarik (Journal of University Medical & Dental College, 2019)
OBJECTIVE: To determine the eﬀect of Trans PRK on tear ﬁlm stability. STUDY DESIGN: Pre and post test design. SETTING: The study was conducted in Madinah Teaching Hospital, Faisalabad. PERIOD: From October 2017 to May 2018. MATERIALS AND METHODS: Thirty patients having refractive errors with age from 18-44 years were selected in this study on the basis of inclusion and exclusion criteria by using Schirmer II test and Tear Break up Time Test (TBUT). After informed consent, demographic data, including name, age, sex and address for all the cases was obtained. Trans PRK refractive surgery was done. The patients were then followed up at one week, three month and six months after Trans PRK to determine the tear ﬁlm stability. The data was analyzed by using SPSS version 23. Categorical variables presented as frequency and percentages and numerical variables presented as mean ± standard deviation. RESULTS: All the pre-operative Schirmer II test values were more than 10mm/5sec and tear breakup time were more than 10 seconds. The schirmerII test value was nearly stable after surgery, but the mean TBUT was 12 seconds at pre operation, 7 seconds at post operative one week and 9 seconds at three month, and 10 seconds at six months post operatively. A comparison between three pairs of Schirmer test in mm was, Pair 1 between one week pre Trans PRK 13 ± 1.531 mm and one week post Trans PRK 9.00 ± 3.553 mm, the mean diﬀerence 4.000 mm shows that p-value <0.00. Pair 2 between one week pre Trans PRK 13 ± 1.531 mm and three months post Trans PRK 11.07 ± 2.753 mm the mean diﬀerence 1.933 mm shows that p-value <0.00. Pair 3 between one week pre Trans PRK 13 ± 1.531 mm and six month post Trans PRK 12.07 ± 1.311 mm, the mean diﬀerence 0.933 mm shows that p-value <0.02 statistically signiﬁcant indicates that Schirmer test gradually reached nearly to the normal values with time as after 6 months. Similarly, a comparison between three pairs of Tear break up test (TBUT) in seconds was, Pair 1 between one week pre Trans PRK12.00 ± 1.365 sec and one week post Trans PRK7.05 ± 1.147 sec the mean diﬀerence 4.950 sec shows that p-value <0.00. Pair 2 between one week pre Trans PRK12.00 ± 1.365 sec and three month post Trans PRK9.00 ± 1.722 sec the mean diﬀerence 3.000 sec shows that p-value <0.00. Pair 3 between one week pre Trans PRK12.00 ± 1.365 sec and six month post Trans PRK10.06 ± 2.642 sec the mean diﬀerence 1.943 sec shows that p-value<0.002 indicates that Tear break up test values ﬂuctuated with time. The relationship between TBUT and dry eye symptoms in which 25 (41.67%) eyes out of 60 showed a decreased TBUT and 23 (38.33%) eyes out of 60 complained dry eye symptoms and 18 (78.26 %) among the 23 eyes with dry eye symptoms had decreased TBUT (p-value <0.05). CONCLUSION: This study concluded that the Trans PRK had altered tear ﬁlm stability. In comparison of tear ﬁlm stability before and after Trans PRK there was signiﬁcant change in TBUT test values of post Trans PRK than Pre-Trans PRK values.